2015
DOI: 10.1007/978-3-319-24553-9_73
|View full text |Cite
|
Sign up to set email alerts
|

A Random Riemannian Metric for Probabilistic Shortest-Path Tractography

Abstract: Abstract. Shortest-path tractography (SPT) algorithms solve global optimization problems defined from local distance functions. As diffusion MRI data is inherently noisy, so are the voxelwise tensors from which local distances are derived. We extend Riemannian SPT by modeling the stochasticity of the diffusion tensor as a "random Riemannian metric", where a geodesic is a distribution over tracts. We approximate this distribution with a Gaussian process and present a probabilistic numerics algorithm for computi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…This strategy offers novel ways to quantify and visualize uncertainty arising from the numerical computation and allow marginalization over a space of feasible solutions. Hauberg et al [40] extended this work and incorporated data uncertainty in DTI by sub-sampling the diffusion gradients and solving the noisy ODE. Several other studies using the shortest path algorithms in fiber tracking can be found in the literature [39,63].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy offers novel ways to quantify and visualize uncertainty arising from the numerical computation and allow marginalization over a space of feasible solutions. Hauberg et al [40] extended this work and incorporated data uncertainty in DTI by sub-sampling the diffusion gradients and solving the noisy ODE. Several other studies using the shortest path algorithms in fiber tracking can be found in the literature [39,63].…”
Section: Methodsmentioning
confidence: 99%
“…Color coding the fiber tracts according to their seed points [22] does not suffice to minimize the complexity of the visualization. Schober et al [88] and Hauberg et al [40] used wobbly spaghetti plot that emphasize the fact that the individual resulting paths cannot be considered as real fibers in the brain which is a common misinterpretation in spaghetti plot. Instead, they are uncertain estimates of fibers.…”
Section: Global Uncertainty Visualizationmentioning
confidence: 99%
“…The most successful area of research to date has been on the development of Bayesian methods for global optimisation [Snoek et al, 2012], which have become standard to the point of being embedded into commercial software [The MathWorks Inc.] and deployed in realistic [Acerbi, 2018, Paul et al, 2018 and indeed high-profile [Chen et al, 2018] applications. Other numerical tasks have yet to experience the same level of practical interest, though we note applications of probabilistic methods for cubature in computer graphics [Marques et al, 2013] and tracking [Prüher et al, 2018], as well as applications of probabilistic numerical methods in medical tractography [Hauberg et al, 2015] and nonlinear state estimation in an industrial context.…”
Section: Killer Appsmentioning
confidence: 99%
“…Finally, second order tensors are in 1-1 correspondence with covariance matrices, and any metric on second order tensors therefore also defines a metric on centered multivariate normal distributions. Statistics on probability distributions have many possible applications, from population statistics on uncertain tractography results represented as Gaussian Processes [27,20] via evolutionary algorithms for optimization [19], to information geometry [3].…”
Section: Why Are Second Order Tensors Still Interesting?mentioning
confidence: 99%